If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Mp + mz = r Reorder the terms: mz + pM = r Solving mz + pM = r Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1pM' to each side of the equation. mz + pM + -1pM = -1pM + r Combine like terms: pM + -1pM = 0 mz + 0 = -1pM + r mz = -1pM + r Divide each side by 'z'. m = -1pz-1M + rz-1 Simplifying m = -1pz-1M + rz-1
| lnx^7-10lnx=1 | | 3+2*[(2+1)*5+8]= | | -5x+2=-2x-31 | | 2y+6+8y+10+y+32=180 | | X^2+13x-64=0 | | 5m-28=-33+6m | | 3x^2+56=-136 | | 9n-23=17+n | | 2y^2-4y-8=y^2+y | | (1.8X+0)-(1.4X+0.6)= | | 2(x+4)-126=0 | | 3+y=10+3 | | m^2+m+.25=0 | | p+12=24 | | (5-4x)(x-5)=0 | | 12x^2-52x+48=0 | | ln(11x-7)=0 | | 3y-8y=12 | | 6x+5=54-x | | 0.2x+0.01=0.2y | | 20%-39.99= | | 7-9x+10+5x+5x-3=9+2*4 | | 2x-3=1.4 | | -4x*x-4x= | | 1/7(r-49)=6/7 | | 15x^5-21x^4-18x^3=0 | | -12y+7=-13y+1 | | 32/8-23/4= | | 2x+6+3x=x+4x+4.5 | | 7x-1=1+10x | | 4x+4=9x+3-5x+1 | | 3xXx=30 |